Therapeutic effects of Silybum marianum in the treatment of liver fibrosis and cirrhosis - Awan, Asim; Saeed, Aftab; Usmanghani, Khan; Rafiq, Muhammad (Asian Journal of Medical Sciences, 2019)
Background: Cirrhosis is the late, symptomatic stage of chronic liver disease which occurs when scar tissue (fibrosis) largely replaces healthy liver tissue, compromising the function of the organ and predisposing to liver failure and hepatocellular carcinoma. It is mainly caused by hepatitis B and C virus infections or prolonged excessive consumption of alcohol. Aims and Objective: To study the therapeutic effects of Silybum marianum on liver fibrosis and cirrhosis in patients with chronic hepatitis C virus infection with Child Pugh Stage A& B. Materials and Methods: In this study 119 patients were treated for 6 months with Silybum marianum, their Liver stiffness measurements were carried out through Fibroscan, which is a non-invasive technique to assess liver fibrosis. Liver Fibrosis Scores viz; Aspartate aminotransferase/platelet ratio index(APRI) and fibrosis index based on four factors(FIB-4) were also employed at baseline and end of treatment. Results: Pre-treatment Liver Stiffness Measurement (LSM) score was 22.54 kilopascals(kPa) and post treatment was 17.30 kPa, a statistically significant change of 5.24 kPa (P ˂ 0.01) was observed, the mean percent change was 23.24%, its impact was observed in all METAVIR stages. Of the 72 (60.5%) patients with LSM ≥ 12.5 kPa (cirrhosis) at baseline 23 (32%) proved to have no cirrhosis (≥ 1 decrease in fibrosis stage) at post treatment. Similarly, 19 patients moved to stage F0-F1, 28 patients in F2 and 23 in F3. Overall fibrosis stage was improved (≥ 1 decrease in fibrosis stage) in 46 (38.7%) of 119 patients after 6 months of treatment. Serum fibrosis scores APRI and FIB-4 significantly decreased in comparison to baseline values. APRI values drooped from 1.24 to 0.83. FIB-4 score changed from 3.90 to 2.10. Conclusion: Our result suggests significant improvement with Silybum marianum in the patients status of liver fibrosis and cirrhosis associated with hepatitis C related chronic liver disease. Silybum marianum shows therapeutic effect in real life setting on the entire aspect of disease, as evaluated with the fibroscan and serum fibrosis score.